Prognostic significance of tumor markers in T4a gastric cancer - Liu Xiaowen; Cai Hong; Wang Yanong (World Journal of Surgical Oncology, 2012)
Abstract Background The clinical importance of preoperative tumor markers remain elusive in gastric cancer. The aim of this study was to evaluate the prognostic value of AFP, CEA, CA19-9, and CA50 in T4a stage gastric cancer. Methods Two hundred and seventy-three T4a gastric cancer patients who underwent curative D2 gastrectomy between 1996 and 2005 were evaluated. The correlation between tumor markers and clinicopathologic characteristics and prognostic value of preoperative tumor markers were investigated. Results Correlation analysis showed that AFP was associated with Borrmann type (P = 0.010); CEA with sex (P = 0.029), tumors site (P = 0.014), and N stage (P = 0.001); CA19-9 with age (P = 0.047), tumor site (P = 0.011), lymphovascular invasion (P = 0.004), and N stage (P = 0.000); CA50 with age (P = 0.017), tumor site (P = 0.004), tumor size (P = 0.014), and N stage (P = 0.000). Multivariate analysis showed that the positivity of preoperative CEA, CA19-9, and CA50 were major independent poor prognostic factors of patients with T4a stage gastric cancer. Conclusions Preoperative serum tumor marker might be a candidate for the staging system in addition to conventional factors.